PENGGUNAAN METODE FMECA (FAILURE MODES EFFECTS CRITICALITY ANALYSIS) DALAM IDENTIFIKASI TITIK KRITIS DI INDUSTRI KEMASAN - Arif Rahman; Farah Fahma (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
XYZ is a company engaged in packaging, especially for pharmaceuticals. The company has recorded an overall defective product known as end to end waste. During 2019 the average end to end waste was 12.37%, while the target of company management was 9%. The objective of this research is to minimize defective products and to find out what types of defects occur in the production process. The method used in this research is FMECA (Failure Modes, Effects and Critically Analysis), which is the development of the FMEA (Failure Mode and Effect Analysis) method which functions to make analyzes from production tools or processes, types of defects to the effects that arise as a result. of the defect, but also to determine the critical point. The results of the analysis that has been carried out using the FMEA method with RPN (Risk Priority Number) calculations, then analysis with the Pareto diagram and criticality matrix, the researcher gets 10 priority failure modes, namely the machine often stops due to a lot of paper dust, too high piles, unstable colors because there is a change in ink, the non-stop feeder is damaged, the front lay and side lay are unstable from the printing process, the side lay sensor does not work, the actual chiller temperature with the display is not the same, the paper is untidy from the printing process, the paper is untidy from the calendering process, and the chiller is leaking. The researcher also gave recommendations, namely making a Standard Operation Procedure (SOP) for handling dusty paper, submitting complaints to suppliers regarding paper quality, providing a printing unit, and training for dusty paper handling. Keywords: criticality matrix, FMECA, risk priory number, pareto diagram